Sinergi Memperkuat Character Building melalui Literasi Budaya di Perguruan Tinggi - Kristina Kristina (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Character building can be strengthened and developed through various programs and activities provided in schools and universities. Purpose Research. Universitas Surabaya is one of the universities committed to providing character education to the academic community with the aim of creating good and excellent characters so that they can adapt and interact with the diversity that exists in the campus and wider community. Synergy between units and the academic community is needed to achieve individuals who have good character and morals. Methods. In this study, the author uses a literature review approach. Result. The results of this study are expected to make the UBAYA Library an integral part of the university and also have an important role in supporting the character building program that has been implemented. Conclusion. Through the Cultural Literacy program, the UBAYA library is committed to collaborating with other units aimed at making "library as cultural hubs”.Keywords: character building, cultural literacy, academic library